Interplay of governance elements and their effects on deforestation in tropical landscapes: Quantitative insights from Ecuador. (December 2021) - Fischer, Richard; Tamayo Cordero, Fabian; Ojeda Luna, Tatiana; Ferrer Velasco, Rubén; DeDecker, Maria; Torres, Bolier; Giessen, Lukas; Günter, Sven
Highlights: Specific forest governance elements act conjointly, interact positively and probably reinforce each other. Tenure and participation were related to decreasing deforestation. A differentiated view on single governance components is needed for development work and research. Direct drivers like agriculture and infrastructure were more strongly linked to deforestation than governance elements. Results are based on a comprehensive, empirical field study in Ecuadorian lowland forests covering 160, 000 ha. Abstract: After state-centered and market-centered approaches have driven international development cooperation activities in previous decades, improved governance has now come into the focus as a means to help reversing global trends of tropical deforestation. Yet, "good governance" remains a normative, broad and often underspecified concept consisting of a wide range of elements and implicit value judgements. Specific knowledge is missing on the relative importance of single elements, on their interdependencies and their specific effects. Following an analytical approach, we aimed to investigate if single governance elements affect each other and whether they relate to decreasing deforestation. We conducted a quantitative field study in twelve selected landscapes across 160, 000 ha of tropical lowland forest in Ecuador. We mapped governance arrangements and land use in participatory exercises. The performance of single governance elements including tenure, forest management practices, law enforcement, institutions, and participation was quantified based on the governance assessment framework of the World Resource Institute. We assessed context information and used satellite based deforestation data. Principal component analysis showed that all governance elements loaded positively on the first axis. This shows that specific governance elements acted conjointly. They are in general not antagonistic, but interact positively and might reinforce each other. Policy and development work may therefore focus on a smaller number of well-selected governance elements. High performance of specific governance elements, in particular tenure and participation was linked to reduced deforestation. This supports the notion of a number of governance elements as being indeed "good" for low deforestation. This functional understanding draws a more differentiated picture for single governance elements and supports outcome oriented decisions instead of value-oriented principles that underlie "good governance". Direct deforestation drivers such as agriculture and infrastructure explained larger shares of deforestation as compared to governance. A number of conclusions and recommendations for the specific governance situation in tropical lowland forests of Ecuador are given.